2017
DOI: 10.1038/srep43569
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression guided chemical profiling of living cells by the simultaneous observation of Raman scattering and anti-Stokes fluorescence emission

Abstract: Our current understanding of molecular biology provides a clear picture of how the genome, transcriptome and proteome regulate each other, but how the chemical environment of the cell plays a role in cellular regulation remains much to be studied. Here we show an imaging method using hybrid fluorescence-Raman microscopy that measures the chemical micro-environment associated with protein expression patterns in a living cell. Simultaneous detection of fluorescence and Raman signals, realised by spectrally separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…It is evident from the figure that the lowest detectable concentration of the PCNA substrate for R6G molecules is about 10 nM. It is important to note that the use of carbon quenched the fluorescent property of R6G molecules, even including anti-Stokes fluorescence in the case of excitation at 785 nm caused by the thermal excitation (Boltzmann distribution) that allows the excitation photon energy to be smaller than the energy gap between the ground state and an excited state 29 , indicating the ability of the PCNA substrate to analyze biomolecules which are mostly fluorescent ( Supplementary Fig. 10, Supplementary Note 12).…”
Section: High Reproducibility and Fluorescence Quenching Of The Pcnamentioning
confidence: 99%
“…It is evident from the figure that the lowest detectable concentration of the PCNA substrate for R6G molecules is about 10 nM. It is important to note that the use of carbon quenched the fluorescent property of R6G molecules, even including anti-Stokes fluorescence in the case of excitation at 785 nm caused by the thermal excitation (Boltzmann distribution) that allows the excitation photon energy to be smaller than the energy gap between the ground state and an excited state 29 , indicating the ability of the PCNA substrate to analyze biomolecules which are mostly fluorescent ( Supplementary Fig. 10, Supplementary Note 12).…”
Section: High Reproducibility and Fluorescence Quenching Of The Pcnamentioning
confidence: 99%
“…They are also important in intercellular cell signaling, apoptosis, and metabolizing polyunsaturated fatty acids. A recent study has shown that it can also act as an antioxidative enzyme [ 17 , 18 , 19 , 20 , 21 ]. Cytochromes are classified based on their lowest electronic energy absorption band in their reduced state: cytochrome P450 (450 nm), cytochrome c (550 nm), cytochromes b (≈565 nm), cytochromes a (605 nm).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the 2‐mono‐cyanoresazurin (R 2 ) shows a negative Stokes shift about −841 cm −1 , known as anti‐Stokes fluorescence (ASF) emission, which is a fascinating phenomenon in the study of fluorescence materials. It is a single‐photon excitation process and arises due to the hot‐band absorption, as reported in several organic dyes [50,51] . For clarity, the overlap profile of A–E spectrum (intensity vs .…”
Section: Resultsmentioning
confidence: 99%